The male of Culicoides irwini Spinelli & Wirth (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2001)
The previously unknown male of the biting midge Culicoides irwini Spinelli & Wirth is described and illustrated from specimens collected associated with females at EI Bolson, Rio Negro Province, Argentina, which represents the southernmost record of this species. The species is compared with C. caridei (Brethes) and C. patagoniensis Ronderos & Spinelli.